2018
DOI: 10.1101/494674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of the mayfly Cloeon dipterum as a new model system to investigate insect evolution

Abstract: The great capability of insects to adapt to new environments promoted their extraordinary diversification, resulting in the group of Metazoa with the largest number of species distributed worldwide. To understand this enormous diversity, it is essential to investigate lineages that would allow the reconstruction of the early events in the evolution of insects. However, research on insect ecology, physiology, development and evolution has mostly focused on few well-established model species. The key phylogeneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Genome sequencing and assembly. Genomic DNA was extracted from C. dipterum adult males from an inbred line kept in the laboratory for seven generations 10 . Illumina and Nanopore technologies were used to sequence the genome (Supplementary Data 2-4 and Supplementary Note 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome sequencing and assembly. Genomic DNA was extracted from C. dipterum adult males from an inbred line kept in the laboratory for seven generations 10 . Illumina and Nanopore technologies were used to sequence the genome (Supplementary Data 2-4 and Supplementary Note 1).…”
Section: Methodsmentioning
confidence: 99%
“…We found that more than half of CS genes, and among these, nearly 80% of OBPs (147 out of 276 CS genes and 121 out of 152 OBPs included in the soft-clustering analysis) were mostly assigned to just four clusters (18, 12, 9 and 10), all of them related to nymphal or pre-nymphal stages. Cluster 10 contained genes that had a peak of expression at 14 dpf stage, just prior to the hatching of the first swimming nymph 10 , and genes in clusters 9, 12 and 18 were most highly expressed during nymphal stages (Fig. 3b).…”
Section: Role Of Odorant-binding Protein Genes During Aquatic Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, care should be taken if the results from these tests are to be used for regulatory purposes. However, a recently published protocol for culturing C. dipterum (Almudi et al 2019) should be evaluated with respect to its potential use in aquatic toxicity testing.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 17, 2021. ; https://doi.org/10.1101/2021.03.17.435759 doi: bioRxiv preprint subimaginal stage that lasts about 1 day, and the adult that can live 10-20 days, which is exceptionally long for mayflies (14).…”
Section: Introductionmentioning
confidence: 99%